2019
DOI: 10.1021/acs.chemrev.9b00153
|View full text |Cite
|
Sign up to set email alerts
|

Designer Peptide and Protein Dendrimers: A Cross-Sectional Analysis

Abstract: Dendrimers have attracted immense interest in science and technology due to their unique chemical structure that offers a myriad of opportunities for researchers. Dendritic design allows us to present peptides in a branched three-dimensional fashion that eventually leads to a globular shape, thus mimicking globular proteins. Peptide dendrimers, unlike other classes of dendrimers, have immense applications in biomedical research due to their biological origin. The diversity of potential building blocks and innu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 248 publications
(355 reference statements)
0
77
0
Order By: Relevance
“…It was demonstrated that peptide dendrimers have high biocompatibility and are resistant to proteolytic digestion [ 166 , 167 , 168 ]. This resulted in the application of peptide dendrimers for the delivery of drug and gene materials [ 169 ]. An effort was made for delivery of HSP27-siRNA using peptide dendrimers in the treatment of PCa.…”
Section: Nano-vehiclesmentioning
confidence: 99%
“…It was demonstrated that peptide dendrimers have high biocompatibility and are resistant to proteolytic digestion [ 166 , 167 , 168 ]. This resulted in the application of peptide dendrimers for the delivery of drug and gene materials [ 169 ]. An effort was made for delivery of HSP27-siRNA using peptide dendrimers in the treatment of PCa.…”
Section: Nano-vehiclesmentioning
confidence: 99%
“…It is interesting to note, that this protein-type dendrimer category (i.e., Denkewalter type) has received substantially less attention in the literature compared to traditional Tomalia and Newkome type, symmetrical branch cell dendrimers. According to a recent review article by Haridas et al [31], a SciFinder search from 1993 to 2019 reveals only 282 research publications related to asymmetrical branch cell Denkewalter-type dendrimers have appeared in the literature. In contrast, during this same time (i.e., 1990-2019), >50,000 publications have been documented for symmetrical branch cell containing Tomalia-type dendrimers.…”
Section: Figure 5 Comparison Of Densities As a Function Of Generatiomentioning
confidence: 99%
“…Earlier interest in poly(peptide) type dendrimers was documented largely by Tam et al [44,45] lysine core dendrimers with tetrapeptides and octapeptides were more soluble in water, more stable to proteolysis and less toxic to human cells than their linear polymeric analogs; comparable antimicrobial potency was demonstrated by Jezek et al [46]. However, recent work by Haridas et al [31] exhaustively reviewed the area of peptide/protein dendrimers and has clearly revealed significant new interest in this overlooked area of dendrimer science. More specifically, Urbanczyk-Lipkowska [47] have described the synthesis and evaluation of amphiphilic peptide dendrimer as specific antimicrobials effective against drug-resistant bacteria [48]; whereas, Reymond et al [49,50] reports the structure-activity relationships for a library of single component, well-defined peptide dendrimers, which are equivalent to Lipofectamine L2000 as a transfection vector for siRNA.…”
Section: Historical Overview: First Divergently Synthesized Dendrimermentioning
confidence: 99%
“…The success of amphiphilic dendrimer-based delivery systems has encouraged further exploitation of their diversity. Peptide dendrimers are type of dendrimers composed of amino acids in branch fashion and hold great potentials for biomedical applications by virtue of their unique properties such as protein-mimic structural features, good biocompatibility, and high resistance to proteolytic digestion (Bracci et al 2003;Crespo et al 2005;Darbre and Reymond 2006;Sadler and Tam 2002;Sapra et al 2019). Novel-designed amphiphilic dendrimers featuring peptide dendrimers as hydrophilic heads are expected to show suitable flexibility, good safety profile, and protein-like properties; therefore, they are of particular interest for siRNA delivery (Dong et al 2020;Heitz et al 2019;Inoue et al 2008;Malhotra et al 2012).…”
Section: Introductionmentioning
confidence: 99%